Contabilidad y marketing: buscando un denominador común - Murphy, David S. (2012)
Accounting and marketing are very different disciplines. The analysis of customer profitability is one concept that can unite accounting and marketing as a common denominator. In this article I search for common ground between accounting and marketing in the analysis of customer profitability to determine if a common denominator really exists between the two. This analysis focuses on accounting profitability, customer lifetime value, and customer equity. The article ends with a summary of what accountants can do to move the analysis of customer value forward, as an analytical tool, within companies.